Relationship between income distribution and job satisfaction :the mediating role of the distributive justice - Wong,, Hai Nguon. (Universiti Malaysia Sarawak, UNIMAS, 2010)
This study aims to study the mediating role of the distributive justice onto the relationship between income distribution and job satisfaction. This study had been carried out at the Mulu Press Sdn Bhd (Sin Chew Daily), Kuching. 87 employees had been made up from the organization to participate in this study. Data was collected by using the survey question naire method which gathered the respondents’ demographic, perception toward organization income distribution, distributive justice in the organization and the job satisfaction of respondents in the organization. Pilot study was carried out onto 20 responde nts in order to test the reliability of the questionnaire before conducting the actual study. The data gathered from the actual study was analyzed using SPSS version 16.0. The direct relationship between income distribution and job satisfaction was determi ned by using the Pearson Correlation Analysis where the mediating role of distributive justice into the relationship was tested using the Stepwise Regression Analysis. The findings from this study indicated that the is a significant relationship between th e income distribution and job satisfaction. Not only that, the result also confirmed that the distributive justice fully mediate the relationship between income distribution and job satisfaction. Besides, the findings from the study had indicated that the respondents’ position as a determinant toward the relationship between income distribution, distributive justice and job satisfaction where respondents’ monthly salary as a determinant to the respondents’ perception toward the organization’s level of distr ibutive justice. Thus, this study supports the empirical study which carried by the previous researchers.